2021
DOI: 10.1017/s1352465821000126
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise as an add-on treatment to cognitive behavioural therapy for anxiety: a systematic review

Abstract: Background: Cognitive behavioural therapy (CBT) is currently the treatment of choice for most anxiety disorders. Yet, with recovery rates of approximately 50%, many patients fail to achieve complete remission. This has led to increased efforts to enhance treatment efficacy. Physical exercise (PE) has in recent years been advocated as means to augment the effects of CBT for anxiety disorders. PE appears to reduce anxiety through other mechanisms than CBT, some of which might also have the potential to augm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…A meta-analysis including 13 trials suggested a short-term effect of exercise on depression ( 59 ). Frederiksen et al reviewed eight articles and suggested that PA was more beneficial for anxiety populations compared to cognitive behavioral therapy ( 60 ). Recent systematic review by Ng et al indicated that PA is a beneficial and well-tolerated intervention for children and adolescents with ADHD ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including 13 trials suggested a short-term effect of exercise on depression ( 59 ). Frederiksen et al reviewed eight articles and suggested that PA was more beneficial for anxiety populations compared to cognitive behavioral therapy ( 60 ). Recent systematic review by Ng et al indicated that PA is a beneficial and well-tolerated intervention for children and adolescents with ADHD ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies have directly examined the relationship between physical exercise and life satisfaction, a number of studies have examined the positive effects of physical exercise on mental health. For example, moderate physical exercise can promote the improvement of individual psychological regulation ability, reduce the level of depression and anxiety, and can significantly improve the individual’s quality of life ( Kvam et al, 2016 ; Frederiksen et al, 2021 ; Nguyen et al, 2021 ). When individuals are physically healthy, emotionally sound and have a high quality of life, they may also be more satisfied with their current life.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is associated with wellbeing, mood and mental health, such as depression and anxiety [39]. It has been demonstrated that regular exercise performed for at least 10 weeks (at least 30 min a day, three to four times a week) can effectively reduce anxiety levels [40].…”
Section: Discussionmentioning
confidence: 99%